Contactin-Associated Protein 1 (CNTNAP1) Mutations Induce Characteristic Lesions of the Paranodal Region. Issue 12 (December 2016) - Vallat, Jean-Michel; Nizon, Mathilde; Magee, Alex; Isidor, Bertrand; Magy, Laurent; Péréon, Yann; Richard, Laurence; Ouvrier, Robert; Cogné, Benjamin; Devaux, Jérôme; Zuchner, Stephan; Mathis, Stéphane
Abstract : Congenital hypomyelinating neuropathy is a rare neonatal syndrome responsible for hypotonia and weakness. Nerve microscopic examination shows amyelination or hypomyelination. Recently, mutations in CNTNAP1 have been described in a few patients. CNTNAP1 encodes contactin-associated protein 1 (caspr-1), which is an essential component of the paranodal junctions of the peripheral and central nervous systems, and is necessary for the establishment of transverse bands that stabilize paranodal axo-glial junctions. We present the results of nerve biopsy studies of three patients from two unrelated, non-consanguineous families with compound heterozygous CNTNAP1 mutations. The lesions were identical, characterized by a hypomyelinating process; on electron microscopy, we detected, in all nodes of Ranvier, subtle lesions that have never been previously described in human nerves. Transverse bands of the myelin loops were absent, with a loss of attachment between myelin and the axolemma; elongated Schwann cell processes sometimes dissociated the Schwann cell and axon membranes that bound the space between them. These lesions were observed in the area where caspr-1 is located and are reminiscent of the lesions reported in sciatic nerves of caspr-1 null mice. CNTNAP1 mutations appear to induce characteristic ultrastructural lesions of the paranodal region.